An analysis of subsidies within the plastics recycling industry - Black, David (School of Economics, 2016)
Polyethylene terephthalate (PET) is widely used in the manufacture of food and beverage containers, in addition to a variety of fibres. PET is considered to be 100% recyclable and can be recycled into a number of different end-use streams: bottle-to-bottle; bottle-to-foodgrade, or bottle-to-fibre. In South Africa, the PET Recycling Company (trading as PETCO) was established to avoid the possibility of government-imposed punitive legislation and to alleviate the impact of PET-based litter. PETCO generates revenue through the collection of voluntary levies from PET manufacturers and supports the recycling of PET through the administration of recycling subsidies and the unlocking of constraints in the PET recycling value chain. This study sets out to describe the PET recycling industry and empirically assess the effectiveness of PETCO's recycling subsidies through regression analysis. As a background to the regression analysis, the study builds the theory behind production and cost function analysis (in addition to the associated duality theory). However, due to the combination of the research question and the limited data availability, an alternative model was adopted, in order to explain as much variation in production tonnages as possible.